Core-shell polytetrafluoroethylene @ phenolic resin composites: Structure and tribological behaviors. (April 2020) - Yang, Yawen; Wang, Honggang; Ren, Junfang; Gao, Gui; Chen, Shengsheng; Wang, Na; Zhao, Gengrui; Wang, Jinqing
Abstract: Polytetrafluoroethylene @ phenolic resin (PTFE@PR) core-shell particles were successfully synthesized through a versatile one-pot method, which were investigated in tribological characteristics. The core-shell structure was characterized by transmission electron microscopy (TEM), fourier-transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS). The results demonstrated that core-shell composites possess the lower friction coefficient and better anti-wear performance. Friction coefficient of the composite is about 0.178 as low as pure PTFE at 50 N and 0.033 m/s. Meanwhile, the wear volume of the composite was measured at 0.59 mm 3 by rubbing 1 h, which is merely a fifteenth of pure PTFE (8.94 mm 3 ). The chemical action of core-shell composites resulted in the uniform and integrate transfer film, so that outstanding tribological performances of core-shell composites were exhibited. Graphical abstract: Image 1 Highlights: The chemical combination of hard and soft phase particles with core-shell structure can improve the self-lubricating properties and the mechanical strength of materials. A newly core-shell polytetrafluoroethylene @ Phenolic Resin (PTFE@PR), which not only solves PTFE's disadvantage of poor dispersion, but also endows PTFE with excellent wear resistance, thus providing a thought for developing good lubricating materials. Friction coefficient of the core-shell composite is about 0.178 as low as pure PTFE at 50N load and 0.033m/s velocity, the wear volume of the composite was measured at 0.59mm 3 by rubbing 1 h., which is merely a fifteenth of pure PTFE(8.94mm 3 ). The chemical action of the core-shell composites resulted in the uniform and integrated transfer film.